Determination of some heavy metals in some vegetable samples grown around gwaigwaye dam - Mustapha, Aminu; Dahiru, Abdulhamid; Rawayau Zainab, Kabir (International Journal of Advanced Chemistry, 2024)
Consumption of vegetables contaminated with heavy metals poses a serious health risk such as cancer and kidney failure, this highlights the need for monitoring of these metals in vegetables. This study aimed at determining the concentrations of Cadmium, Nickel, Copper, Cobalt, Lead and Zinc in Cabbage, Lettuce and Moringa oleifera leaves grown around Gwaigwaye dams. These vegetables were collected, prepared, digested and analyzed using microwave plasma atomic emission spectroscopy. The results obtained were in the following ranges, 0.018±0.03 to 0.021±0.01 mg/kg for Cd, 0.00±0.00 to 0.19±0.01 mg/kg for Co, 0.00±0.00 to 0.086±0.00 mg/kg for Pb, 0.03±0.00 to0.9±0.00 mg/kg for Ni, 0.21±0.01 to 1.92±0.00 mg/kg for for Cu and 0.00±0.00 to 0.23±0.03 mg/kg for Zinc in cabbage, lettuce and moringa oleifera leaves obtained farmlands around gwaigwaye dam. Fortunately, the levels of these metals fell within the acceptable limits of FAO/WHO. The Analyzed vegetables are free from toxic metals and therefore suitable for human consumption. P- Values obtained from the statistical analysis were greater than 0.05, the differences in the concentrations of the metals observed were therefore not statistically significant.